Approaches to managing disturbance and change: Resilience, vulnerability and adaptability - Daniel Callo-Concha (University of Bonn, Center for Development Research (ZEF), 2014)
The concepts of resilience, vulnerability and adaptability have been used for a long time by several disciplines in relation to the characteristics of a system regarding its ability to react to a changing surrounding. Studies on the ecological resilience of species and ecosystems or on the socio-economic vulnerability of populations are not infrequent, on the contrary, they are well-established in research and scientific communities. Nevertheless, since these concepts were first applied in interdisciplinary research a few years ago, they have gained great popularity, become widely utilized, and are often considered as surrogates of sustainable behaviour, based on the understanding that a highly resilient, little vulnerable and very adaptable system would then be likely able to last longer performing the expected roles. This rapid expansion created several other needs, such as methods for classification, evaluation and analysis, implementation guidelines, etc. In practice, this led to a large and diverse set of definitions and methodological tools with a large degree of overlapping, and often a limited capacity to address the questions inherent to these systems. The purpose of this working paper is therefore to compile and structure the concepts, operational tools and premises of implementation of the main concepts that address disturbance and change, i.e., resilience, vulnerability and adaptability, in the interdisciplinary scientific arena. Although focused on concepts, the basis of this working paper is operational. The 'know-how' is highlighted in order to extract from the review criteria to develop and promote sustainability in practice. Hence, the concepts described are illustrated utilizing relevant examples in general scientific case studies.
Keywords: 330